(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the prevalence and some factors related to hypertension in people aged 40 years and older in Ba Vi district, Hanoi city, in 2023. Methods: A cross-sectional descriptive study with analysis was carried out through clinical examination and face-to-face interviews with 400 people aged 40 years and older to determine the rate and some factors related to hypertension. Results: The rate of hypertension in the study subjects (Blood Pressure from 140/90mmHg or higher) was 36.75%. The number of people with normal blood pressure was 63.25%. The rate of hypertension in the 61-70 age group was 38.78%, 51-60 age group was 26.53%, 41-50 age group was 19.05%. The rate of hypertension in men was 40.85% (87/213), and in women was 32.09% (60/187). Some factors related to hypertension have been identified, including People’s knowledge about hypertension OR = 3.6, 95% CI: 2.362-5,570, p<0.001; People’s Practice prevention of hypertension, OR = 4.5, 95% CI: 2.888-6.909, p<0.001; Adherence to antihypertensive treatment OR = 3.7, 95% CI 2.191-5,169, p<0.001; Regular physical exercise: OR = 1.5 95% CI 1.037- 2,378, p < 0.05. Conclusion: The rate of hypertension in people aged 40 and older in Ba Vi district, Hanoi city, is relatively high (36.75%). The rate of hypertension is related to knowledge, practice, adherence to treatment, disease prevention, and regular physical exercise.